Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1089/ham.2016.0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Blood Flow on Pulmonary Circulation Before and During High Altitude Acclimatization

Abstract: Prolonged altitude exposure leads to a persistent increase in Ppa and PVR without affecting right heart function and is fully reversible within 1 week after return to SL. The thigh cuff release maneuver-induced increase in cardiac output suggests a preserved ability of pulmonary circulation to cope with sudden remarkable increase in pulmonary blood flow throughout acclimatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…In support of our finding of preservation in responsiveness of the pulmonary circulation, Hilty et al (2016) studied healthy volunteers by right heart catheterization after 3 weeks at 3600 m. They found that while PA pressures were mildly elevated, when the pulmonary circulation was challenged with a brief 2.5 l min −1 increase in cardiac output by transient thigh-cuff occlusion there was no increase in PA pressure. In this regard, our findings of maintained responsiveness to changes in inspired oxygen are similar and indicate that the pulmonary vascular pressures, although greater over this time, do not become permanently fixed at a higher resistance.…”
Section: Circulating Biomarker Concentrations At Different Testingmentioning
confidence: 54%
“…In support of our finding of preservation in responsiveness of the pulmonary circulation, Hilty et al (2016) studied healthy volunteers by right heart catheterization after 3 weeks at 3600 m. They found that while PA pressures were mildly elevated, when the pulmonary circulation was challenged with a brief 2.5 l min −1 increase in cardiac output by transient thigh-cuff occlusion there was no increase in PA pressure. In this regard, our findings of maintained responsiveness to changes in inspired oxygen are similar and indicate that the pulmonary vascular pressures, although greater over this time, do not become permanently fixed at a higher resistance.…”
Section: Circulating Biomarker Concentrations At Different Testingmentioning
confidence: 54%
“…In humans, remodelling of the pulmonary arterioles has been indirectly demonstrated during constant exposure to a high altitude environment over several weeks (Hilty et al . ). However, remodelling of pulmonary arterioles and systemic capillary angiogenesis are not necessarily regulated by the same mechanisms, and the timeframe of such processes in animal and human models may diverge.…”
Section: Discussionmentioning
confidence: 97%
“…Cardiac output at rest is expected to decrease towards SL values after an initial increase in well‐acclimatized lowlanders at moderate altitude (Hilty et al . ), as well as at extreme altitude (Reeves et al . ), whereas, in expedition settings, several previous studies have reported a decrease in cardiac output compared to baseline after 10–15 days (Wolfel et al .…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate water loss and blood concentration is conducive to increase the efficiency of red blood cells carrying oxygen, improving the ability of acclimatization, which may be very important for the early migratory population (Yang F. et al, 2016). In contrast, excessive suppression of thirst, can also cause more serious water metabolic disorders, such as dehydration and abnormal water distribution, which is related to deep vein thrombosis (Gupta and Ashraf, 2012; Hull et al, 2016) and high altitude pulmonary edema (Sawka et al, 2015; Hilty et al, 2016). …”
Section: Introductionmentioning
confidence: 99%